2019
DOI: 10.1021/acs.iecr.9b01239
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Gasification for Waste-to-Fuels Applications

Abstract: This paper firstly examines the experimental results from a 16 hours plasma assisted gasification trial for conversion of refuse derived fuel (RDF) into syngas suitable for biofuel production in a pilot plant. In particular the work focuses on the effect on the concurrent ash vitrification and tar reforming processes on the general composition of a syngas stream produced in a fluidised bed gasifier. The effect of plasma on tar reforming is showed by continuous monitoring of gas composition before and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…The raw syngas, containing mostly hydrogen, carbon monoxide, carbon dioxide, and a variety of hydrocarbons including problematic tars, is further treated in a tar-reformer, in this case powered by thermal plasma, at 1200 °C to separate solid particulates and ashes from the stream, while reforming the tars into additional useful syngas. 37 Gasification parameters including temperature of gasifier, equivalence ratio, and syngas composition are in line with those in the literature for MPW gasification. 10 The exiting hot syngas is cooled (down to 200 °C), and the heat is recovered and recirculated to the energy intensive CCS stages.…”
Section: Mpw Gasification For Hydrogen Production With Ccs (H 2 W/ccs)supporting
confidence: 81%
See 1 more Smart Citation
“…The raw syngas, containing mostly hydrogen, carbon monoxide, carbon dioxide, and a variety of hydrocarbons including problematic tars, is further treated in a tar-reformer, in this case powered by thermal plasma, at 1200 °C to separate solid particulates and ashes from the stream, while reforming the tars into additional useful syngas. 37 Gasification parameters including temperature of gasifier, equivalence ratio, and syngas composition are in line with those in the literature for MPW gasification. 10 The exiting hot syngas is cooled (down to 200 °C), and the heat is recovered and recirculated to the energy intensive CCS stages.…”
Section: Mpw Gasification For Hydrogen Production With Ccs (H 2 W/ccs)supporting
confidence: 81%
“…Most of these plants utilize a steam-oxygen blown fluidized bed gasifier operated at 700–800 °C to successfully gasify polymeric chains down to a syngas stream. The raw syngas, containing mostly hydrogen, carbon monoxide, carbon dioxide, and a variety of hydrocarbons including problematic tars, is further treated in a tar-reformer, in this case powered by thermal plasma, at 1200 °C to separate solid particulates and ashes from the stream, while reforming the tars into additional useful syngas . Gasification parameters including temperature of gasifier, equivalence ratio, and syngas composition are in line with those in the literature for MPW gasification .…”
Section: Technological Aspectsmentioning
confidence: 66%
“…The establishment of flaming combustion in the freeboard also leads to the generation of undesired pollutants, such as NO x [10,27] and SO x [28]. Furthermore, several studies have shown that the volatiles released within the bed evolve in form of endogenous bubbles, which further enhance segregation of the feedstock [21][22][23]29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The main products of plasma gasification include a tar-free synthesis gas (syngas), composed mainly of hydrogen (H2) and carbon monoxide (CO), and an inert and vitrified slag. The syngas can potentially be used for energy production or the production of chemicals, such as bio-hydrogen (Amaya-Santos et al, 2021;Materazzi et al, 2019b), bio-syngas (bioSNG) to replace natural gas (Materazzi et al, 2018), as well as other biofuels (Materazzi, 2019;Materazzi et al, 2019a). The vitrified slag can instead be processed for the production of aggregates or higher value-added construction products such as inorganic polymers (Danthurebandara et al, 2015b;Evangelisti et al, 2015a;Materazzi et al, 2016).…”
Section: Plasma Gasification For Integrated Solid Waste Managementmentioning
confidence: 99%